2010
DOI: 10.1016/j.exppara.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of two Trypanosoma cruzi zymodeme 3 strains

Abstract: Two Trypanosoma cruzi Z3 strains, designated as 3663 and 4167, were previously isolated from insect vectors captured in the Brazilian Amazon region. These strains exhibited different infection patterns in Vero, C6/36, RAW 264.7 and HEp-2 cell lineages, in which 3663 trypomastigote form was much less infective than 4167 ones. A proteomic approach was applied to investigate the differences in the global patterns of protein expression in these two Z3 strains. Two-dimensional (2D) protein maps were generated and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Differences in cruzipain expression were correlated with differential virulence for mice of T. cruzi isolates of Z3 (TcIII and IV) [50]. A proteomic analysis suggested that significant differences in the expression of cruzipain by isolates of TcIII and TcIV (Z3) could also contribute to their differential infectivity to cells [51]. Interestingly, proteolytic activity was lower in the virulent T. cruzi CL strain compared to the non-virulent CL-14 clone [52].…”
Section: Introductionmentioning
confidence: 97%
“…Differences in cruzipain expression were correlated with differential virulence for mice of T. cruzi isolates of Z3 (TcIII and IV) [50]. A proteomic analysis suggested that significant differences in the expression of cruzipain by isolates of TcIII and TcIV (Z3) could also contribute to their differential infectivity to cells [51]. Interestingly, proteolytic activity was lower in the virulent T. cruzi CL strain compared to the non-virulent CL-14 clone [52].…”
Section: Introductionmentioning
confidence: 97%
“…For example, serine proteases, DNase II and trypsin were identified as the early specific diagnostic antigens of trichinellosis by twodimensional electrophoresis (2-DE) and Western blot . Different strains of Trypanosoma cruzi zymodeme were analyzed by 2-DE and cruzipain was identified as an important antigen among these proteins from T. cruzi (Kikuchi et al, 2010). In this study, we performed differential proteomics and immunoproteomics approaches to identify differentially expressed proteins in three developmental stages, and immunogenic proteins were recognized by rabbit and grouper anti-sera.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is involved in the conversion of L-arginine to phosphoarginine. It also participates in the oxidative response and infectivity, as it was upregulated in two highly virulent strains (Kikuchi et al 2010 ). The absence of arginine kinase in mammalian cells, together with its importance in parasite ATP synthesis, credits this enzyme as a potential target for new chemotherapies (Silber et al 2005 ;Sodré et al 2009 ).…”
Section: Molecular Candidates For Drug Interventions and Vaccine Devementioning
confidence: 97%
“…In trypanosomatids, genomic analysis has demonstrated the presence of diverse calpains (Ersfeld et al 2005 ), whose function is associated with differentiation and infectivity in T. cruzi (Ennes-Vidal et al 2010. Evidence of the presence of a calpain-like cysteine peptidase in different parasite forms, together with the absence of a similar sequence in humans, suggests its potential as a drug target (Atwood et al 2005 ;Andrade et al 2008 ;Sant'Anna et al 2009 ;Sodré et al 2009 ;Kikuchi et al 2010 ).…”
Section: Molecular Candidates For Drug Interventions and Vaccine Devementioning
confidence: 98%
See 1 more Smart Citation